Detection of phytophthora cactorum in the irrigation water in commercial orchards of 'Bartlett' pear in Villa Regina, Rio Negro - Rivero, Victoria Ileana; Giayetto, Alejandro Lorenzo; Rossini, Mirta Noemi; Vera Macaya, Diana Lorena (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010